Tidal turbine versus wind turbine drive train testing – synergies and challenges (Proceedings of the European Wave and Tidal Energy Conference, 2025)
Climate change is one of the greatest threats faced by the modern world. The world must increase the use of renewable energy to meet the 1.5 °C target of the Paris Agreement. One renewable energy source with good potential is tidal energy. Compared to the established renewable energy sources such as solar and wind, tidal energy is highly predictable, providing a stable and secure power conversion. Despite a global capacity of up to 1200 TWh/year, only about 40 MW of tidal energy capacity has been installed as of now. The main reasons for the slow adoption of the technology are the uncertainties regarding operating and maintenance costs, which result in a low willingness to invest among investors.A cost-efficient approach for proving the reliability of tidal turbine drive trains is the use of system test benches. Currently, no specific tidal turbine system test bench exists. Due to the similarities in the systems, existing wind turbine system test benches are being used for tidal turbine testing to avoid expenditures on testing infrastructure. Although wind and tidal turbines share similarities in design, like the drive train architecture or the blades that convert kinetic energy to electricity, they differ in detail. Exemplary differences are the number of blades or the load transfer path from the nacelle to the support structure. The load transfer path is particularly different for floating tidal turbines, as the tidal turbine moves more freely through the water than wind turbines with static towers. Furthermore, the non-torque loads (NTLs) are much higher than for wind turbines of similar power levels due to the larger density of water compared to air. Besides the higher density of water, there are phenomena in the underwater environment, such as surface waves, which do not occur in the environment of wind turbines and lead to additional NTLs for the tidal turbine drive train. The described differences and influences on the drive train NTLs must be identified, analyzed, and incorporated into an optimal test bench design and realistic load cases. The test bench design must replicate the effects of the modified load transfer path, and the load case must include all relevant NTLs. To date, there is no method to support the adaptation of wind turbine system test benches to tidal turbine testing or to define realistic NTLs.To address this research gap, this paper analyzes the differences in the design of tidal and wind turbines. Additionally, the differences between the subsea and the above sea level environment are examined that cause additional NTLs for the drive train. In contrast to wind turbines, no dominant design is established for tidal turbines. Therefore, the Orbital Marine’s 02-X is used as an exemplary tidal turbine. A simulation-based method is developed to evaluate the effects of the tidal turbine specifics on the system test bench designs. Furthermore, the method supports the transfer of effects unique to tidal turbines or the effect of the modified load transfer path to NTLs, which can be applied on wind turbine system test benches.